Comparison of Biofilm Formation and Antibiotic Resistance Pattern in Catheter Associated and Non-Catheter Associated Urine Infection by Enterococci species - Suchi, Surovi Era; Uddin, Bhuiyan Mohammad Mahtab; Yeasmin, Mst Marufa; Mahjabin, Mosfika (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Biofilm are associated with many medical conditions including indwelling medical devices, dental plaque, upper respiratory tract infection, peritonitis and urogenital infections and microorganisms growing in a biofilm are intrinsically more resistant to antimicrobial agents than planktonic cells. Objective: The aim of the study was to investigate that biofilm formation and antibiotic resistance by Enterococci species is common in urine of catheterized patients and more than urine of non-catheterized patients. Methodology: This cross-sectional study was carried out in the Department of Microbiology at Dhaka Medical College, Dhaka, Bangladesh. All the suspected cases of urinary tract infection patients were selected as study population. Among the Enterococci, biofilm detection was done by tissue culture plate method. Susceptibility to antimicrobial agents of all isolates were done by Kirby-Bauer modified disk-diffusion technique. Results: Biofilm formation and antibiotic resistance by Enterococci was more in catheter associated urine than catheter non associated urine. Conclusion: The purpose of the study was to show biofilm producing Enterococci and antibiotic resistance pattern of them. Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):110-113